Testicular microlithiasis: Case report and literature review - W. Akhter; S.A.A. Khan; F.R. Khan; A. Younis; S.M.J. Zeb Khan (African Journal of Urology, 2012)
We present an interesting case of bilateral microlithiasis. Microlithiasis is usually considered a benign condition with no need for follow-up. However, when a patient with testicular microlithiasis has a positive family history of testicular cancer, such patients should be followed up closely to detect the development of testicular cancer.